A Comparative Study of Representation of Nationalism and Ethnicity in Koirala’s Sumnima and Pradhan’s In the Battle of Kirtipur - Prasad Adhikary, Dr. Ramesh (International Journal of Humanities and Education Development (IJHED), 2020)
The present research paper makes a comparative study of representation of nationalism and ethnicity in Bishweshwar Prasad Koirala's Sumnima and Hridaya Chandra Singh Pradhan's In the Battle of Kirtipur. These literary texts present the relationship of conflict between nationalism and ethnicity. The reason of conflict is either to preserve the prehistoric identities or to possess power. In construction and representation of nationalism and ethnicity, Koirala gives emphasis on their religious aspects while Pradhan focuses on historical and political aspects.